Standard specification for Cold-Formed Welded and Seamless Carbon Steel Structural Tubing in Rounds and Shapes (American Society of Testing Materials, 2009)
This specification covers cold-formed welded and seamless carbon steel round, square, rectangular, or special shape structural tubing for welded, riveted, or bolted construction ofbridges and buildings, and for general structural purposes.